Reducing arthritis fatigue impact: two-year randomised controlled trial of cognitive behavioural approaches by rheumatology teams (RAFT). Issue 4 (11th April 2019) - Hewlett, Sarah; Almeida, Celia; Ambler, Nicholas; Blair, Peter S; Choy, Ernest H; Dures, Emma; Hammond, Alison; Hollingworth, William; Kadir, Bryar; Kirwan, John Richard; Plummer, Zoe; Rooke, Clive; et al.
Abstract : Objectives: To see if a group course delivered by rheumatology teams using cognitive-behavioural approaches, plus usual care, reduced RA fatigue impact more than usual care alone. Methods: Multicentre, 2-year randomised controlled trial in RA adults (fatigue severity> 6/10, no recent major medication changes). RAFT (Reducing Arthritis Fatigue: clinical Teams using CB approaches) comprises seven sessions, codelivered by pairs of trained rheumatology occupational therapists/nurses. Usual care was Arthritis Research UK fatigue booklet. Primary 26-week outcome fatigue impact (Bristol RA Fatigue Effect Numerical Rating Scale, BRAF-NRS 0–10). Intention-to-treat regression analysis adjusted for baseline scores and centre. Results: 308/333 randomised patients completed 26 week data (156/175 RAFT, 152/158 Control). Mean baseline variables were similar. At 26 weeks, the adjusted difference between arms for fatigue impact change favoured RAFT (BRAF-NRS Effect −0.59, 95% CI –1.11 to -0.06), BRAF Multidimensional Questionnaire (MDQ) Total −3.42 (95% CI –6.44 to -0.39), Living with Fatigue −1.19 (95% CI –2.17 to -0.21), Emotional Fatigue −0.91 (95% CI –1.58 to -0.23); RA Self-Efficacy (RASE, +3.05, 95% CI 0.43 to 5.66) (14 secondary outcomes unchanged). Effects persisted at 2 years: BRAF-NRS Effect −0.49 (95% CI −0.83 to -0.14), BRAF MDQ Total −2.98 (95% CI −5.39 to -0.57), Living with Fatigue −0.93 (95% CI −1.75 to -0.10), Emotional Fatigue −0.90 (95% CI −1.44, to -0.37); BRAF-NRS Coping +0.42 (95% CI 0.08 to 0.77) (relevance of fatigue impact improvement uncertain). RAFT satisfaction: 89% scored > 8/10 vs 54% controls rating usual care booklet (p<0.0001). Conclusion: Multiple RA fatigue impacts can be improved for 2 years by rheumatology teams delivering a group programme using cognitive behavioural approaches. Trial registration number: ISRCTN52709998 .